Fabrication of Hydrogel Beads Entrappted by Mesoporous Silicates Nanoparticles for pH-sensitive and Sustained Release of Indomethacin - Deng, Zhijian; Zhang, Wengzong; Lu, Yizhong; Zhang, Yongheng; Lu, Zhongmin; Pei, Sujuan (Asian Journal of Chemistry, 2014)
In this study, hydrophobic indomethacin was quantitative loaded onto various mesoporous silicates nanoparticles by the wetness impregnation. The DSC results of indomethacin-loaded mesoporous silicates nanoparticles exhibited the amorphous state of drugs and thus might increase its dissolution and bioavailability. The release assays of indomethacin from these mesoporous silicates nanoparticles indicated that both the pore size and the surface functionalization of mesoporous silicates nanoparticles could affect their release rate. Furthermore, these indomethacin-loaded mesoporous silicates nanoparticles were entrapped into chitosan/alginate hydrogels and formed a series of hydrogel beads. The swelling studies indicated that the incorporation of mesoporous silicates nanoparticles had no influence on the swelling behaviors of hydrogel beads. The resultant beads displayed pH-sensitive and sustained-release of hydrophobic indomethacin and thus the combination of chitosan/alginate hydrogels and mesoporous silicates nanoparticles might serve as a potential oral hydrophobic drug delivery system.